Etiological factors of acute pancreatitis in our setting - Delgado, Bolívar (Cirugía del Uruguay, 1975)
F'iftythree. cases of acute pancreatitis, which occurred in the last 10 years were reviewed, all with confirmed diagnosis by laparotomy or necropsy. The etiologic factors were analyzed as they appear in our environment and are compared with data published by other authors. In the first place we find biliary diseases ( 69.8 % ) principally ga!l bladder lithiasis ( 54%), particularLy the small stone variety ( 71 % ) . Common bile duct lithiasis was found in 16.9 %, with 5.6 % of papillar stones. Although alcoholism is hardly considered in this country, it seems to be an importan! ethiological factor ( 18. % ) mainly in males. There is no record of other etiologies and in 11.3 % it was not possible to determine the cause of pancreatitis.